2003
DOI: 10.1002/jccs.200300037
|View full text |Cite
|
Sign up to set email alerts
|

Rice Bran as an Excellent Sorbent for Heavy Metals from Aqueous Media, 2. Determination of Related Parameters

Abstract: In part 2 of this report related parameters of the rice bran (as a sorbent of heavy metals) such as exchange capacity, distribution coefficients and isotherms, etc. were studied. The obtained results show that selectivity of the bran towards heavy metals such as Cu(II), Cd(II), Fe(III), Ni(II), Zn(II) and Pb(II) is very high. Also, distribution coefficients between aqueous solution and bran are more than 10 4 so that all cations are completely adsorbed by the bran in relatively low concentrations. The principa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Therefore, to avoid formation of copper hydroxide, we have worked at below pH 4.5. However, Farajzadeh (2003) in his study reported for removal of copper up to pH 10 having very low concentration of copper on rice bran. This was most likely the combined effect of sorption and the formation of precipitation.…”
Section: Effect Of Phmentioning
confidence: 86%
See 1 more Smart Citation
“…Therefore, to avoid formation of copper hydroxide, we have worked at below pH 4.5. However, Farajzadeh (2003) in his study reported for removal of copper up to pH 10 having very low concentration of copper on rice bran. This was most likely the combined effect of sorption and the formation of precipitation.…”
Section: Effect Of Phmentioning
confidence: 86%
“…This fact has been largely ignored in previous studies [12,21]. This work revealed that the charge on the copper complex played a key role in the sorption process.…”
Section: Removal Of Anionic and Cationic Species Of Coppermentioning
confidence: 92%
“…Biosorption is a process that utilizes biological materials as adsorbents, and several researchers have studied this method as an alternative technique to conventional methods for heavy metal removal from wastewater. [1][2][3][4][5][6][7] The binding mechanisms of heavy metals by biosorption could be explained by the physical and chemical interactions between cell wall ligands and adsorbates by ion exchange, complexation, coordination and microprecipitation. The diffusion of the metal from bulk solution to active sites of biosorbents occurs predominantly by passive transport mechanisms, 8 and various functional groups such as carboxyl, hydroxyl, amino and phosphate existing on the cell wall of biosorbents can bind the heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…The rice bran was activated according to the method given by Farajzadeh, et al 25,26 as follows: The rice bran was treated with saturated sodium chloride solution for one hour. Then the solution was filtered and in order to remove the excess sodium chloride the bran was washed thoroughly with distilled water.…”
Section: Preparation Of Microcolumnmentioning
confidence: 99%
“…The activated rice bran, a natural, inexpensive and environmentally friendly byproduct of rice was shown to be a good sorbent for heavy metals from aqueous media. 25,26 However to the best of our knowledge such material has not been used as packing material for microcolumn preconcentration and quantification of cations at trace levels. Rice bran contains different vitamins, carbohydrates, and potassium, nitrogen and phosphorus compounds, which have no pollution effect and are nutritious to the plants.…”
Section: Introductionmentioning
confidence: 99%